2007
DOI: 10.1002/adem.200600177
|View full text |Cite
|
Sign up to set email alerts
|

Damping Properties of Nanoporous Carbon‐Cyclohexane Mixtures

Abstract: Using liquids in mounting stages, packaging layers, helmets and healthcare pads, etc. has been a common engineering practice. [1] Usually, a "liquid damper" contains a sealing layer and a liquid core, which can nearly perfectly fit with the target to be protected. As a result, the contact area is maximized and thus the contact pressure is lowered. Damages associated with interface mismatches that commonly exist in solid systems, especially in systems of changing configurations, are also largely reduced. Additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…[33][34][35][36] Even if liquids of larger surface tensions are utilized, the maximum energy absorption efficiency is only about 100 J/g. 37,38 The high energy absorption performance of the nanoporous silica gel should be attributed to the small nanopore size, the relatively large porosity, as well as the high network strength.…”
Section: Resultsmentioning
confidence: 99%
“…[33][34][35][36] Even if liquids of larger surface tensions are utilized, the maximum energy absorption efficiency is only about 100 J/g. 37,38 The high energy absorption performance of the nanoporous silica gel should be attributed to the small nanopore size, the relatively large porosity, as well as the high network strength.…”
Section: Resultsmentioning
confidence: 99%
“…They are also much more cost-efficient, which is critical to large-scale engineering applications, such as liquid foundations, protection layers for highway bridges and buildings, etc. However, although at macroscopic length scale it was reported that a carbon material may be hydrophobic [13,14], in a nano-environment, pressureinduced wetting can be difficult [15]. For instance, in a SEM study, Rossi et al [16] argued that carbon nanotubes were wettable in water, which was in agreement with the conclusion of Dujardin et al [17] that carbon nanotubes can be wetted by liquids with surface tensions smaller than 130-170 mJ/m 2 .…”
Section: Introductionmentioning
confidence: 78%
“…where ξ 1 and ξ 2 are the free energies of state 1 and state 2, respectively; P is the applied pressure, V is the volume of the water; γ is the excess solid-liquid interfacial tension; A is the associate solid-liquid interface area; Δμ is the specific free energy difference; and K is the bulk modulus of the gel, which is around 0.1 GPa. 12 The 2 nd , 3 rd , 4 th , and 5 th terms at the RHS of Eq. (F-1) capture the external work, the solid-liquid interaction, the confinement effect of the PIMA-Na gel, and the strain energy, respectively.…”
Section: F Developing Solid-like Energy Absorption Systemsmentioning
confidence: 99%
“…If the cell wall size is large, the first-order mode is most energetically favorable. 12 Recent research has shown that if soft joints are installed, they would trigger higher-order buckling modes under a relatively low pressure, and thus both temporal and spatial characteristics of buckling patterns are adjusted. 13 Decreasing the cell size can be of a similar effect.…”
Section: J Compression Of Nanoporous Particlesmentioning
confidence: 99%